Macroeconomic uncertainty and investment relationship for Turkey - Pelin Öge Güney (Universitas Islam Indonesia, 2020)
Macroeconomic uncertainties are expected to affect investment decisions. This study analyzes the effect of the real exchange rate, inflation, and growth uncertainties on private investment in Turkey, an emerging country. While a generalized autoregressive conditional heteroskedasticity (GARCH) model is adopted to measure uncertainties, the existence of a long-run relationship of the variables is assessed using the bound testing approach. Finally, an error correction model is estimated to capture the dynamic relationship. Findings/Originality: The results for the short-run dynamic estimation show that both inflation and real exchange rate uncertainties have a significant negative effect on investments. As for the long-run equilibrium, exchange rate, inflation, and growth uncertainties have a negative impact on private investments. The application of inflation targeting and exchange rate stabilization policy might effectively reduce uncertainty on investments, thus supporting economic growth in the short term.